2019
DOI: 10.4414/smw.2019.20091
|View full text |Cite
|
Sign up to set email alerts
|

Swiss paediatrician survey on complementary medicine

Abstract: BACKGROUND: In Switzerland, complementary medicine (CM) is officially recognised within the healthcare system and mainly practised in an integrative manner, in conjunction with conventional medicine. As in other countries, there is high demand for and use of CM with children. However, there has so far been no research into the attitude towards, training in and offer of CM among paediatricians in Switzerland. Our study addresses this gap by investigating these topics with an online survey of paediatricians in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
(68 reference statements)
1
19
0
1
Order By: Relevance
“…A escolha por uso de plantas medicinais inclui alto custo dos medicamentos sintĂ©ticos, inacessibilidade das instituiçÔes e serviços de saĂșde e aceitabilidade cultural do sistema tradicional (TSOBOU; MAPONGMETSEM; DAMME, 2016). Das prĂĄticas complementares, a fitoterapia Ă© a mais utilizada e difundida, pelas suas extensas peculiaridades, visto que ela envolve desde a cadeia produtiva de plantas medicinais a terapĂȘuticas (GALVEZ et al, 2017;HUBER et al, 2019;HABIMORAD et al, 2020). O seu uso na assistĂȘncia Ă  saĂșde torna-se mais efetiva quando em consonĂąncia com o saber empĂ­rico, pois se torna uma prĂĄtica de cuidado que valoriza o saber popular (CRUZ, 2016;GALVEZ et al, 2017).…”
Section: Resultsunclassified
“…A escolha por uso de plantas medicinais inclui alto custo dos medicamentos sintĂ©ticos, inacessibilidade das instituiçÔes e serviços de saĂșde e aceitabilidade cultural do sistema tradicional (TSOBOU; MAPONGMETSEM; DAMME, 2016). Das prĂĄticas complementares, a fitoterapia Ă© a mais utilizada e difundida, pelas suas extensas peculiaridades, visto que ela envolve desde a cadeia produtiva de plantas medicinais a terapĂȘuticas (GALVEZ et al, 2017;HUBER et al, 2019;HABIMORAD et al, 2020). O seu uso na assistĂȘncia Ă  saĂșde torna-se mais efetiva quando em consonĂąncia com o saber empĂ­rico, pois se torna uma prĂĄtica de cuidado que valoriza o saber popular (CRUZ, 2016;GALVEZ et al, 2017).…”
Section: Resultsunclassified
“…However, the number of licensed medical doctors who practice CAM or offer CAM services without full accreditation is likely higher. A representative study of pediatricians in Switzerland reported that 23% of pediatricians had attended CM training, but only 8% had a federal certificate in one or more of these methods [26]. The same study found that 97% of pediatrician respondents reported patients and parents inquiring about CAM, 65% were interested in pursuing CAM training, 16% provided CAM to their patients, and more than 50% used CAM for themselves or their families.…”
Section: Methodsmentioning
confidence: 99%
“…Be aware of one of the major determinants of vaccine hesitancy: the prevalent perception that the health authorities are collaborating with and/or influenced by vaccine manufacturers On a larger scale, our ongoing National Research Program on vaccine hesitancy [13,14] has recruited a network of more than 150 medical professionals throughout Switzerland, including more than 40 CAM practitioners. Given the popularity and interest towards CAM of the Swiss population [21,22] and from pediatricians [26], the incorporation of CAM perspectives and engagement with practitioners of both CAM and biomedicine into vaccination communication strategies is, in our view, a feasible, innovative, and reasonable approach to addressing VH in the Swiss context.…”
mentioning
confidence: 99%
“…In Switzerland, which is known for its high standards in child health care [ 4 ], PIM is an integral part of the health care system [ 3 ]. This is shown, on the one hand, by the significant prevalence of complementary medicine use within the Swiss population in general [ 5 – 7 ] and among children and adolescents in particular, concerning the whole spectrum from primary care to highly specialized medicine [ 8 – 13 ]. According to data from the federal office of statistics, the utilization of complementary medicine is constantly increasing during the last two decades [ 14 ].…”
Section: Introductionmentioning
confidence: 99%